Implementasi Supervisi Manajerial dalam Meningkatkan Kinerja Guru di MTSN 3 Sumedang - Linda Tazkiyatul Munawaroh; Muhammad Alamsyah; Muhammad Fikri Shidiq; Muhammad Amar Khana (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2023)
Managerial supervision has an important role in improving the quality of education in Madrasah Tsanawiyah. Target managerial supervision includes two kinds of the principal as manager education, and the 8 national education standards in school. By functionit known that the role of a superintendent as managerial supervisor is as a consultant, managing, fostering, and accompanies in dealing with common problems on managerial governance in school. The research was conducted at MTsN 3 Sumedang. The method usedin this research is using a qualitative approach. Data collection procedures were carried out through observation, interviews, and documentation studies. The results of the study show that: 1) The implementation program of managerial supervision in MTsN 3Sumedang by the principal aligns with the stages of planning, implementation, assessment, reporting, and follow-up. 2) The managerial supervision of the principal of MTsN 3 Sumedang has adhered to the 8 national education standards. 3) Managerial supervision in 3 Sumedang serves as the foundation for maintaining the quality of education in MTsN 3 Sumedang and its development plan.